The Expanding Cell Diversity of the Brain Vasculature - Ross, Jayden M.; Kim, Chang; Allen, Denise; Crouch, Elizabeth E.; Narsinh, Kazim; Cooke, Daniel L.; Abla, Adib A.; Nowakowski, Tomasz J.; Winkler, Ethan A. (Frontiers in Physiology, 2020)
The cerebrovasculature is essential to brain health and is tasked with ensuring adequate delivery of oxygen and metabolic precursors to ensure normal neurologic function. This is coordinated through a dynamic, multi-directional cellular interplay between vascular, neuronal and glial cells. Molecular exchanges across the blood-brain barrier or the close matching of regional blood flow with brain activation are not uniformly assigned to arteries, capillaries and veins. Evidence has supported functional segmentation of the brain vasculature. This is achieved in part through morphologic or transcriptional heterogeneity of brain vascular cells – including endothelium, pericytes and vascular smooth muscle. Advances with single cell genomic technologies have shown increasing cell complexity of the brain vasculature identifying previously unknown cell types and further subclassifying transcriptional diversity in cardinal vascular cell types. Cell-type specific molecular transitions or zonations have been identified. In this review, we summarize emerging evidence for the expanding vascular cell diversity in the brain and how this may provide a cellular basis for functional segmentation along the arterial-venous axis.